Tariff revisions and the impact of variability of solar irradiation on PV policy support: The case of Italy. (August 2018) - Monarca, Umberto; Cassetta, Ernesto; Pozzi, Cesare; Dileo, Ivano
Abstract: The solar irradiation is one the most critical parameter to ensure the overall profitability of photovoltaic (PV) projects. During the period of the European solar boom, the PVGIS-3 radiation data have been largely used by policy makers in setting remuneration levels, as well as by project developers, banks and asset managers for professional assessment of the underlying financial return of the investment. High quality and more accurate data included in the updated PVGIS-CMSAF show that solar resources in Europe have been greatly underestimated by PVGIS-3. The present paper evaluates how reported changes in solar irradiation have affected both PV projects profitability and overall costs of subsidy for final consumers. By focusing on a large sample of Italian PV plants, our findings highlight that solar irradiation levels higher than those initially assumed have caused excessive rents and windfall profits for PV project developers thus potentially harming electricity users which are indirectly bearing the burden of the renewable energy sources (RES) incentives. In regulatory contexts suffering from information asymmetries between RES producers and regulatory agencies, support tariff set by public authorities should be periodically revised according to transparent procedures, whenever significant changes in long-term solar irradiation data occur. Highlights: Economic consequences from changes in local availability of solar resources are investigated. Solar irradiation greater than expected have had a relevant impact on the profitability of PV plants. Over-compensation to PV developers and additional costs for electricity users are quantified. A policy intervention to reduce consumers' costs is suggested.